2003
DOI: 10.1111/j.0033-3298.2003.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Administrative Traditions and Policy Change: When Policy Paradigms Matter. The Case of Italian Administrative Reform During the 1990s

Abstract: In recent years a growing number of scholars have developed cognitive and ideational theoretical frameworks for the analysis of policy‐making processes: their underlying belief is that ideas (conceived as beliefs, causal theories and paradigms) really do matter. The concept of policy paradigm has been particularly useful in studying both the contents and dynamics of policy change. The present paper takes this concept, partially reformulates Hall's definition in terms of the distinction between the hegemonic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
136
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(138 citation statements)
references
References 33 publications
0
136
0
2
Order By: Relevance
“…Italy has a strong legalistic administrative tradition and represents a relevant context of study, since it has been often identified as a typical example of Napoleonic country and a medium-intensity adopter of NPM ideas (Hood 1991(Hood , 1995Capano 2003;Pollitt and Bouckaert 2004;Ongaro 2011;Fattore et al 2012, Bellè andOngaro 2014). Moreover, being a civil-law country, Italy has always relied on laws and administrative acts to adopt reforms (Panozzo 1998).…”
Section: Methods Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Italy has a strong legalistic administrative tradition and represents a relevant context of study, since it has been often identified as a typical example of Napoleonic country and a medium-intensity adopter of NPM ideas (Hood 1991(Hood , 1995Capano 2003;Pollitt and Bouckaert 2004;Ongaro 2011;Fattore et al 2012, Bellè andOngaro 2014). Moreover, being a civil-law country, Italy has always relied on laws and administrative acts to adopt reforms (Panozzo 1998).…”
Section: Methods Of the Studymentioning
confidence: 99%
“…The paper explores reforms with novel methodological lenses in a country that has been described as a mild adopter of managerial reforms and a neo-Weberian state (Capano 2003;Kuhlmann 2010;Ongaro 2011). …”
mentioning
confidence: 99%
“…Consequently, the adoption of emergent budgetary tools was initially limited to local level (Ongaro & Valotti, 2008), where governments have "adopted planning and results assessment, budgeting financial autonomy for up to 60% of their resources, and diversified managerial strategies for their public services as far back as 1993" (Lippi, 2003, p. 152). It has also to be noted that until 2003, the 93% of Italian municipalities had implemented an independent unit dedicated to managerial accounting services, while just the 50% of them had adopted innovative accounting methods (Capano, 2003). In terms of accounting reform, in 2005, the city of Pisa was the first local government to consolidate its financial accounts, thanks to the implementation of technical tools designed for a deeper monitoring of financial performances and a better management of achieved results (Kuhlmann, 2010).…”
Section: Accounting Public Policies and Tools: An Italian Overviewmentioning
confidence: 99%
“…While following a consistent policy path, symbolic innovations create a picture of activity but in fact support the status quo. Thus, symbolic innovations serve as negative feedback in order to ensure increasing returns and policy stability (Pierson 2000, Capano 2003, Howlett and Rayner 2006. Second, the process sequencing approach with its application of the punctuated equilibrium model (Haydu 1998, Baumgartner et al 2009) follows the idea of cycles switching between incremental and more radical sequences of change (Howlett 2009).…”
Section: Policy Innovation and Policy Changementioning
confidence: 99%
“…Third, cumulative incrementalism describes a number of approaches all criticising process sequencing on the basis of empirical cases where 'shocks do not always result in institutional change, and institutional change does not always come from such shocks' (Van der Heijden 2010, p. 231, Genschel 1997, Pierson 2004 but rather as a result of cumulative adaption (Coleman et al 1996, Capano 2003, Lee and Strang 2006, Cashore and Howlett 2007. Here, 'bottom-up' processes of increasing returns and policy learning through incremental changes of the meso-level of policy instruments finally reach a tipping point for a more radical change in the instrumental logic at the highest policy level (Pierson 1993, Coleman et al 1996, Howlett and Cashore 2009, Daugbjerg and Sønderskov 2012.…”
Section: Policy Innovation and Policy Changementioning
confidence: 99%